The Location of Cross-Border Mergers & Acquisitions in the USA - Steven Brakman; Harry Garretsen; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2015)
The research on the location choice for Foreign Direct Investment (FDI) is traditionally restricted to a choice between countries. The within-country location choice is less prominent in the literature. If within-country location decisions are considered it is mostly limited to Greenfield investments. The vast majority of FDI, however, takes place in the form of cross-border Mergers & Acquisitions (M&As), and for this form of FDI (empirical) research on location choice within countries has been neglected. In this paper we analyze the within country location-target selection of M&As in the USA. Extending Guadalupe (2012), by introducing location choice, and applying the consequences of super-modularity of our model we analyze the within country location choice of (cross-border) M&As. Using a detailed firm level data set for all manufacturing sector M&As across the USA for the period 1985-2012, we compare location choices of cross-border M&As to that of national M&As. We find that: cross-border M&As are more spatially concentrated than national M&As, that cross-border M&As sort into larger agglomerations across the USA than national M&As, and that for both forms of M&As location specific market access in the USA as well as access to the rest of the world (through transport hubs) are key drivers for target selection.
Keywords: F10; F12; L13; 330; cross-border mergers and acquisitions; location choice; agglomeration